Multisensory Modalities and Modernist Translation. Issue 3 (December 2016) - Brzostowska-Tereszkiewicz, Tamara
Abstract : Multisensory and cross-modal perception have been recognised as crucial for shaping modernist epistemology, aesthetics, and art. Illustrative examples of how it might be possible to test equivalences (or mutual translatability) between different sensual modalities can be found in theoretical pronouncements on the arts and in artistic production of both the avant-garde and high modernism. While encouraging multisensory, cross-modal, and multimodal artistic experiments, twentieth-century artists set forth a new language of sensory integration. This article addresses the problem of the literary representation of multisensory and cross-modal experience as a particular challenge for translation, which is not only a linguistic and cross-cultural operation but also cross-sensual, involving the gap between different culture-specific perceptual realities. The problem of sensory perception remains a vast underexplored terrain of modernist translation history and theory, and yet it is one with potentially far-reaching ramifications for both a cultural anthropology of translation and modernism's sensory anthropology. The framework of this study is informed by Douglas Robinson's somatics of translation and Clive Scott's perceptive phenomenology of translation, which help to put forth the notion of sensory equivalence as a pragmatic correspondence between the source and target texts, appealing to a range of somato-sensory (audial, visual, haptic, gestural, articulatory kinaesthetic, proprioceptive) modalities of reader response.